Possible causes of morbidity and adverse outcomes of COVID-19 in vaccinated elderly patients - M. P. Kostinov; C. Zhang; I. A. Khrapunova; S. R. Raicic; A. S. Pechenik; V. A. Utkin; M. N. Loktionova; A. V. Linok; E. G. Simonova; V. A. Brazhnik (Журнал инфектологии)
A prospective randomized observational study was conducted in cohorts of vaccinated and unvaccinated patients hospitalized in one of the Moscow hospitals and diagnozed with COVID-19 in the period from 06.23.2021 to 01.05.2022.The purpose of the study was to identify the epidemiological features of COVID-19 in vaccinated people and to present scientifically based data on the need for vaccination and its importance in stopping the epidemic process.Materials and Methods. The samples were studied in comparison for a number of indicators: age, clinical condition at admission, the presence and number of concomitant systemic chronic diseases as well as disease outcomes.Results. It was proven that the risk of COVID-19 morbidity in vaccinated people decreased by 1.5 times, mortality by 1.5 times, and hospitalization due to the severity of the condition by 3.1 times. The mortality risk among vaccinated patients shifted to older age (76.9 years), while among unvaccinated patients, the mortality risk was higher for older people (73.7 years), which indicates an increase in life expectancy of vaccinated people.